Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Value Clarification Technique (VCT) pada Pembelajaran Pendidikan Pancasila di Kelas V SD Negeri 08 Campago Ipuh Kota Bukittinggi - Delya, Fathiyah Putri; Rahmatina, Rahmatina (Lembaga Yasin AlSys, 2024)
The research was motivated by the low learning outcomes of students in learning Pancasila education. This study aims to describe the improvement of student learning outcomes in Pancasila education learning with the Matrix Type Value Clarification Technique model in Class V SDN 08 Campago Ipuh Bukittinggi City. This research is a Classroom Action Research that uses qualitative and quantitative approaches. Carried out in two cycles, namely cycle I carried out 2 meetings and cycle II carried out 1 meeting. Each cycle includes four stages, namely planning, implementation, observation, and reflection. The subjects of this study were teachers and students of class V SDN 08 Campago Ipuh with a total of 26 students. Data collection techniques in the form of observation, tests and non-tests. The results showed an increase in a) Teaching Module cycle I with an average of 85.5% (Good), and cycle II 93% (Very Good), b) implementation of learning in the teacher aspect of cycle I with an average of 81.2%, and cycle II 93.7% (Very Good) while the implementation of learning aspects of students cycle I with an average of 81.2% and cycle II 93.7%, c) student learning outcomes in cycle I with an average of 75 (Fair) and cycle II 88 (Good). Based on these results it can be concluded that with the Value Clarification Technique Matrix Type model the learning outcomes of students in learning Pancasila Education can increase.